SAT0470 Matrix Metalloproteinase-3 (MMP-3) Correlates with Low Bone Mineral Density (BMD) at the Lumbar Spine, but not at the Femoral Neck in Patients with Systematic Lupus Erythematosus (SLE). (10th June 2014) - Kishimoto, H.; Nishiyama, S.; Yoshinaga, Y.; Aita, T.; Ohashi, K.; Miyawaki, S.; Miyoshi, S.; Yoshihara, Y.; Toda, M.; Tsuno, M.
Abstract : Background: There are few articles show the difference of risk factor of osteoporosis between the lumbar spine and the femoral neck in SLE patients 1–6 . Objectives: To compare the risk factor of osteoporosis between the lumbar spine and the femoral neck in SLE patients. Methods: Consecutive 39 cases with SLE (mean age 49.1 years, 38 female, one male) who visited our hospital from Jun. 2012 to Dec. 2013 were studied. BMD was measured with dual-energy X-ray absorptiometry at the lumbar spine and the femoral neck, and correlations between BMD and age, disease duration, age of onset, disease activity (SLEDAI), glucocorticosteroid dose, thyroid function (TSH, freeT4), renal function (serum and urine β2-microglobuline, GFR, cystatin C) and other serum factors (C3, C4, 25-hydroxyvitamin D (25(OH)D), calcium, MMP-3) were examined by multivariate analysis. Results: According to the WHO criteria, rates of osteoporosis, osteopenia, and normal BMD at the lumbar spine were 38%, 21%, and 41%, and at the femoral neck, 23%, 44%, and 33%, respectively. By stepwise regression, only MMP-3 negatively correlated with BMD at lumbar spine, but did not with BMD at the femoral neck. Although high rate (74%) of 25(OH)D deficiency were found, there was no correlation between BMD and serum level of 25(OH)D. Conclusions: High prevalence of osteopenia and osteoporosis as well as 25(OH)D were found in patients with SLE. High level of serum MMP-3 may affect on decrease in BMD at lumbar spine, but at the femoral neck in SLE patients. Although the reason is unknown, we have to keep in mind high MMP-3 has possibility the cause of bone fragility at the lumbar spine in SLE patients. References: García-Carrasco M, et al. Osteoporosis in patients with systemic lupus erythematosus. Isr Med Assoc J. 2009; 11:486-91. Furukawa M, et al. Prevalence of and risk factors for low bone mineral density in Japanese female patients with systemic lupus erythematosus. Rheumatol Int. 2011; 31:365-76. Gilboe IM, et al. Bone mineral density in systemic lupus erythematosus: comparison with rheumatoid arthritis and healthy controls. Ann Rheum Dis 2000; 59: 110-15. Lakshminarayanan S, et al. Factors associated with low bone mineral density in female patients with systemic lupus erythematosus. J Rheumatol 2001; 28: 102-8. Bultink, et al. Prevalence of and risk factors for low bone density and vertebral fractures in patients with systemic lupus erythematosus. Arthritis Rheum 2005; 54: 2044-50. Mok CC, et al. Bone mineral density in postmenopausal Chinese patients with systemic lupus erythematosus. Lupus 2005; 14: 106-12. Acknowledgements: - Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2923